2015
DOI: 10.1002/hbm.23071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norepinephrine transporter gene variants on NET binding in ADHD and healthy controls investigated by PET

Abstract: Attention deficit hyperactivity disorder (ADHD) is a heterogeneous disorder with a strong genetic component. The norepinephrine transporter (NET) is a key target for ADHD treatment and the NET gene has been of high interest as a possible modulator of ADHD pathophysiology. Therefore, we conducted an imaging genetics study to examine possible effects of single nucleotide polymorphisms (SNPs) within the NET gene on NET nondisplaceable binding potential (BPND) in patients with ADHD and healthy controls (HCs). Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Contrary to these findings, another recent study indicated highe r NET availability in the thalamus ( Sigurdardottir et al, 2016 ) in healthy [T] carriers, supporting potential alternative explanations. More research considering the distinct underlying network dynamics is necessary to reveal the complex interactions between NET genetics, NET availability and function, and connectivity differences.…”
Section: Discussionmentioning
confidence: 67%
“…Contrary to these findings, another recent study indicated highe r NET availability in the thalamus ( Sigurdardottir et al, 2016 ) in healthy [T] carriers, supporting potential alternative explanations. More research considering the distinct underlying network dynamics is necessary to reveal the complex interactions between NET genetics, NET availability and function, and connectivity differences.…”
Section: Discussionmentioning
confidence: 67%
“…But in line with our hypothesis, we interpreted the observed rapid blood pressure response as being a consequence of higher NE levels at the peripheral effector cells caused by the reduced expression of NET in [T] carriers ( Kim, 2006 ) and consequently impaired reuptake capacity. Another explanation could be that differences in the central NET expression lead to reduced central counter mechanisms for the blood pressure rise in [T] carriers ( Okamoto et al, 2012 ; Sigurdardottir et al, 2016 ). The information about this genetic difference contributes to future individual tailoring of patient medication.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the application of 11 C-MRB in ADHD, a study on 18 F-FMeNER-D 2 PET by Vanicek et al (2014) found no significant difference in either NET availability or distribution in ADHD-relevant regions of the brain. However, Sigurdardottir et al (2016) used it to identify the genotype-dependent difference in NET BP ND between healthy controls and ADHD patients. It provided further evidence of NET imbalance in several brain areas, pointing to epigenetic dysfunction in ADHD (Sigurdardottir et al 2019).…”
Section: F-fmener-dmentioning
confidence: 99%